2003
DOI: 10.1023/a:1021624520740
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Quercetin is a flavonoid molecule ubiquitous in nature and functions as an anti-oxidant and anti-inflammatory agent with little toxicity in vivo and in vitro. Dose- and time-dependent effect of quercetin has been investigated on proinflammatory cytokine expression and NO production, focusing on its effects on the MAP kinases and the NF-kappaB signal transduction pathways in LPS-stimulated RAW 264.7 cells by using RT-PCR and immunoblotting. Quercetin strongly reduced activation of phosphorylated ERK kinase and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
71
0
2

Year Published

2007
2007
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 279 publications
(80 citation statements)
references
References 34 publications
7
71
0
2
Order By: Relevance
“…NF-kB, a nuclear transcription factor, is a regulator of inflammatory processes (Jeong et al, 2014). Previous studies demonstrated that treatment with quercetin inhibits LPS-induced NF-kB activation in RAW 264.7 macrophages (Cho et al, 2003). In the present study, LPS greatly increased NF-kB concentrations in human PBMCs compared with the normal control group.…”
Section: Discussionsupporting
confidence: 54%
“…NF-kB, a nuclear transcription factor, is a regulator of inflammatory processes (Jeong et al, 2014). Previous studies demonstrated that treatment with quercetin inhibits LPS-induced NF-kB activation in RAW 264.7 macrophages (Cho et al, 2003). In the present study, LPS greatly increased NF-kB concentrations in human PBMCs compared with the normal control group.…”
Section: Discussionsupporting
confidence: 54%
“…Recent investigations suggest that tyrosine kinase and MAP kinase pathway might be potential pharmacological targets. 8 Flavonoids are low molecular weight compounds rich in seeds, citrus fruits, red wine, tea, and olive oil. Flavonoids exert several biological activities, which are mainly related to their ability to inhibit enzymes and/or to their antioxidant properties, and are able to regulate the immune response.…”
Section: Introductionmentioning
confidence: 99%
“…Regarding the flavonoids in the extract, quercetin is the predominant flavonoid found. A previous study reported that pretreatment with quercetin significantly inhibited NO production, and iNOS, TNF-, IL-1, and IL-6 expression in the same cell model by inhibiting phosphorylation of Erk1/2 and p-38 MAPK via stabilizing the NF-B/IB complex [19]. Recently, the antioxidant capacity of quercetin was also examined comparing with curcumin on ROS and NO production in LPSstimulated human THP-1 monocytic leukemia cells [20].…”
Section: Discussionmentioning
confidence: 99%